Survivin - an inhibitor of apoptosis and a new therapeutic target in cancer - Pižem, Jože (Radiology and oncology (Ljubljana), 2003)
Survivin is a unique member of the inhibitor of apoptosis (IAP) protein family. It inhibits apoptosis by interfering with post-mitochondrial events during apoptosis, thus blocking activation of caspases. The expression of survivin is among the most tumour specific of all human genes. It is overexpressed in most human cancers but is not detected in most normal tissues. Some molecular mechanisms of survivin upregulation in cancer have been elucidated, including loss of the wild-type p53. Tumours that overexpresssurvivin generally bear a worse prognosis and are associated with resistance to therapy. Its differential expression in caneer versus normal tissues makes survivin detection a useful tool in cancer diagnostics and a promising therapeutic target. Survivin targeting has resulted in increased spontaneous and induced apoptosis and inhibition of tumourgrowth. Some anticaneer drugs currently introduced into clinical practice might well act byinactivaring survivin.
Keywords: Apoptosis; Apoptoza; Beljakovina p53; Cysteine Proteinases; Diagnostic Use; Drug Effects; Drug Therapy; molecular biology; molekularna biologija; Neoplasms; Novotvorbe; onkologija; Protein P53; rak (medicina); Therapeutic Use; therapy; tumor; zdravljenje